Vaccination of rabbits with immunodominant antigens from Sarcoptes scabiei induced high levels of humoral responses and pro-inflammatory cytokines but confers limited protection. Issue 1 (December 2016) - Casais, Rosa; Granda, Victor; Balseiro, Ana; del Cerro, Ana; Dalton, Kevin; González, Roxana; Bravo, Pablo; Prieto, J.; Montoya, Maria
Abstract Background Vaccination is an attractive ecological alternative to the use of acaricides for parasite control. However, effective anti-parasite vaccines against sarcoptic mange have not yet been developed. The purpose of this study was first to identifySarcoptes scabiei immunodominant antigens and second to evaluate them as vaccine candidates in a rabbit/S. scabiei var.cuniculi model. Methods TheS. scabiei Ssλ15 immunodominant antigen was selected by immunoscreening of aS. scabiei var.hominis cDNA. The full-length cDNA was sequenced and cloned into the pGEX vector and the recombinant protein expressed in BL21 (DE3) cells and purified. A vaccination trial was performed consisting of a test group (n = 8) immunised with recAgs (a mix of two recombinant antigens, Ssλ15 and the previously described Ssλ20∆B3) and a control group (n = 8) immunised with PBS. All analyses were performed with R Statistical Environment with α set at 0.050. Results The full-length open reading frame of the 1, 821 nt cloned cDNA encodes a 64 kDa polypeptide, the sequence of which had 96 % identity with a hypothetical protein ofS. scabiei . Ssλ15 was localised by immunostaining of skin sections in the tegument surrounding the mouthparts and the coxa in the legs of mites. Rabbit immunisation with recAgs induced high levels of specific IgG (P < 0.010) and increased levels of total IgEs. However, no significant clinical protection againstS. scabiei challenge was detected. Unexpectedly, the group immunised with the recAgs mix had significantly higher lesion scores (P = 0.050) although lower mean mite densities than those observed in the control group. These results might indicate that the lesions in the recAgs group were due not only to the mites density but also to an exacerbated immunological response after challenge, which is in agreement with the specific high levels of pro-inflammatory cytokines (IL-1 and TNFα) detected after challenge in this group. Conclusions The selected antigens delivered as recombinant proteins had no clinical protective efficacy againstS. scabiei infestation although immunisation reduced mite density. However, these results pave the way for future studies on alternative production systems, adjuvants, delivery methods and combinations of antigens in order to manage stimulation of clinical protective immune responses.